2011
DOI: 10.1002/pro.583
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of aromatic pairs to the folding and stability of long‐lived human γD‐crystallin

Abstract: Human cD-crystallin (HcD-Crys) is a highly stable protein that remains folded in the eye lens for the majority of an individual's lifetime. HcD-Crys exhibits two homologous crystallin domains, each containing two Greek key motifs with eight b-strands. Six aromatic pairs (four Tyr/Tyr, one Tyr/Phe and one Phe/Phe) are present in the b-hairpin sequences of the Greek keys. Ultraviolet damage to the aromatic residues in lens crystallins may contribute to the genesis of cataract. Mutant proteins with these aromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(87 citation statements)
references
References 51 publications
7
80
0
Order By: Relevance
“…In this case, the aggregating protein was human ␥D-crystallin carrying a double-alanine substitution of tyrosine residues, Y92A/Y97A (18,25). Suppression of aggregation by WT CCT5 was similar to that found with WT human ␥D-crystallin (Fig.…”
Section: Resultssupporting
confidence: 48%
“…In this case, the aggregating protein was human ␥D-crystallin carrying a double-alanine substitution of tyrosine residues, Y92A/Y97A (18,25). Suppression of aggregation by WT CCT5 was similar to that found with WT human ␥D-crystallin (Fig.…”
Section: Resultssupporting
confidence: 48%
“…Besides the tyrosine corners, six aromatic pairs (four tyr/tyr, one tyr/phe and one phe/phe) are present in the β-hairpin sequences of the Greek key. The role of these aromatic pairing to the stability of the molecule has been highlighted by Kong and King [41]. The role that trp residues (W) play is also worth commenting upon.…”
Section: Section I: Thementioning
confidence: 97%
“…These studies revealed the significant stabilizing effect of domain interface residues, including hydrophobic residues and glutamines (Flaugh et al, 2005b; Flaugh et al, 2006; Mills-Henry et al, 2007). Substitutions of tyrosine residues have elucidated the contributions of both conserved and variable tyrosine pairs (Kong and King, 2011). Tryptophan residues have been investigated both for their contribution to native-state stability (Kosinski-Collins et al, 2004; Xia et al, 2013); E.S., T. Takata, and J.…”
Section: Introductionmentioning
confidence: 99%